2014
DOI: 10.1002/srin.201300354
|View full text |Cite
|
Sign up to set email alerts
|

Non-Metallic Inclusions in TWIP Steel

Abstract: Twinning induced plasticity (TWIP) steels with excellent strength and elongation properties are expected to be the next generation of automotive high-strength steels. The present work investigates endogenous inclusions formed in Fe-25Mn-3Si-3Al TWIP steels in laboratorial ingot, mold casting after AOD steelmaking and electroslag remelting (ESR) process at industrial plant, respectively. The research shows that AlN and Al 2 O 3 inclusions are found as dominating inclusions, and most of them are AlN, but the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 9 publications
2
33
2
Order By: Relevance
“…In addition, multiphase inclusions containing different combinations of Al 2 O 3 , AlN, and MnS were also observed. Both analysis methods, manual SEM and 3D observation, showed consistent results which were in agreement with the previous studies . Figure shows elemental mappings (Kα1 peaks) of typical multiphase inclusions observed in the steel sample using the manual SEM method.…”
Section: Methodssupporting
confidence: 89%
See 4 more Smart Citations
“…In addition, multiphase inclusions containing different combinations of Al 2 O 3 , AlN, and MnS were also observed. Both analysis methods, manual SEM and 3D observation, showed consistent results which were in agreement with the previous studies . Figure shows elemental mappings (Kα1 peaks) of typical multiphase inclusions observed in the steel sample using the manual SEM method.…”
Section: Methodssupporting
confidence: 89%
“…Gigacher et al also reported the presence of Al 2 O 3 –MnO with AlN and/or MnS, single AlN, and single MnS inclusions in (15–25) Mn–3Al–3Si steels. Several other studies have reported similar types of inclusions present in AHSSs …”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations